Cutaneous manifestations of coronavirus disease 2019 patients in Japan. Issue 9 (10th May 2022) - Tamai, Masakazu; Sakamoto, Rika; Goto, Noriko; Morimura, Osamu; Nishida, Tsutomu; Iwahashi, Hiromi; Yokomi, Akinori
Abstract: Some patients with coronavirus disease 2019 (COVID‐19) develop skin manifestations. There may be regional and racial differences in the frequency and type of COVID‐19‐associated skin manifestations. There are, however, few reports on skin manifestations in COVID‐19 patients in Asia, including Japan. We retrospectively investigated the frequency, type, and clinical course of skin manifestations in Japanese patients with COVID‐19. From 22 February 2020 to 16 August 2021, 738 Japanese patients (median age 59 years, 55% male) with laboratory‐confirmed COVID‐19 on polymerase chain reaction or antigen tests were admitted to our hospital. We mainly admitted patients with mild to moderate severity who had symptoms such as cough, fever, and oxygen demand but did not require mechanical ventilation. A total of 2.8% (21/738) of the COVID‐19 patients treated at our hospital were diagnosed with viral eruptions caused by COVID‐19. Of the 21 patients, 19 developed erythematous papules, and two developed urticaria. There were no cases of pernio‐like lesions, known as COVID toes. The median duration from the onset of other COVID‐19 symptoms to the development of skin manifestations was 9 days. This study revealed that approximately 2–3% of Japanese patients with COVID‐19 developed COVID‐19‐associated viral eruptions, most of which were erythematous papules.